PEMBUATAN KEPUTUSAN, DEMOGRAFIS, DAN KEPUASAN PASCA BELI PADA KELOMPOK LOYAL MEREK DAN TIDAK LOYAL MEREK - Rintar Agus Simatupang; Marlis Ida (Fakultas Bisnis UKDW, 2015)
The objectives of this research were to test difference of decision making on brand loyal group andnon brand loyal group, association between demographical factor and brand loyal group and nonbrand loyal group, and difference in postpurchase satisfaction on brand loyal group with high priceand non brand loyal group with low price. Data analysis technique used were discriminant analysis,Chi-Square, and t-test. Result of the research indicated that there is no difference in shoppingorientation and buying criteria on brand loyal group and non brand loyal group for Jeans and shirtsproducts. Age and income variables had no association with brand loyal group and non brand loyalgroup for Jeans and shirt products. In addition, there was no difference in post-purchase satisfactionbrand loyal group with high price and non brand loyal group with low price for Jeans product, butthere was association for shirt product.Keywords: Brand Loyalty, Shopping Orientation, Buying Criteria, Age, Income, andPost-Purchase Satisfaction